OUTSOURCING IN RETAIL - Radojko Lukić (Economic Review)
Modern strategic techniques have been increasingly applied in recent years, both in manufacture and retail, individually or concurrently. The main goal of their application in the retail business is continuous  improvement, in particular by reducing costs of competitiveness and (business and financial) performance, while increasing customer satisfaction and meeting the needs of customers/consumers. One of the most important strategic techniques increasingly used not only in manufacturing but also in modern retail is outsourcing, which basically involves purchasing goods and/or services from independent external suppliers. The research in contemporary practice of the retail business has revealed that the application of outsourcing technique contributes to stronger commitment of management towards the activities that are the core of competitiveness, reducing costs, improving competitiveness and creating added value. All this has a long-term impact on improving performance in the retail sector. Starting from the developed theory and conducted practical research, this paper emphasizes the importance and specific problems of application of outsourcing the strategic technique in the modern retail. Their knowledge is very important for an effective implementation of outsourcing as a function of improving overall performance in retail. This is especially true for retailers in developing and transition countries, as it is the case, for example, with Serbia, where the use of outsourcing is at a very low level compared to developed countries. In the future, because of its economic importance, outsourcing will certainly be more applied in the retail sector of respective countries, with the expectation of a growing trend at approximately the same level as it is in developed countries in Europe and America.